Hippocampal area CA2: interneuron disfunction during pathological states - Piskorowski, Rebecca A.; Chevaleyre, Vivien (Frontiers in Neural Circuits, 2023)
Hippocampal area CA2 plays a critical role in social recognition memory and has unique cellular and molecular properties that distinguish it from areas CA1 and CA3. In addition to having a particularly high density of interneurons, the inhibitory transmission in this region displays two distinct forms of long-term synaptic plasticity. Early studies on human hippocampal tissue have reported unique alteration in area CA2 with several pathologies and psychiatric disorders. In this review, we present recent studies revealing changes in inhibitory transmission and plasticity of area CA2 in mouse models of multiple sclerosis, autism spectrum disorder, Alzheimer’s disease, schizophrenia and the 22q11.2 deletion syndrome and propose how these changes could underly deficits in social cognition observed during these pathologies.